NAIVE BAYES ALGORITHM TO PREDICT STUDENT SUCCESS IN A COURSE - Evi Ramadhani, Shedriko , Ismail Husein ,Ilka Zufria, Hamidah Nasution (International Journal of Advanced Science and Technology, 2020)
Good coordination between lecturers is needed to ensure the relatively uniform quality of education from the delivery of material by the different lecturers. By knowing the success information from several classes, it is expected that the success of other classes can be predicted. This research is using a quantitative analysis method with Naive Bayes Algorithm methodology in passing decisions on IIT (Introduction to Information Technology ) subject. The result gives the pattern of training data in mean and standard deviation towards three attributes, i.e. tasks, mid-semester and final exam score, which can classify or predict graduation for new data test. The pattern of this equation can also be used for other class classification, on the same or different subjects.